Technical Change, Productivity and Economic Growth - George Korres; Theodoros Iosifides (European Regional Science Association (ERSA), 2003)
This paper investigates the relationship between productivity and technological change. The question that we shall address in this paper, is whether the recent slow down in productivity can be explained by the slow-down of innovation activities. This paper measures technical change through the application of a production function, and the Malqiust index in order to measure the effects of economic growth for European member states. It introduces the reader, first, to some basic elements and concepts that are central to understanding the approach. The characteristics of the innovation process are examined: its nature, sources and some of the factors shaping its development. Particular emphasis is laid on the role of technical change and dissemination based on the fundamental distinction between codified and tacit forms. These concepts recur throughout the paper and particularly in discussions on the nature and specifications of the systems approach. The paper concludes by summarizing some of the major findings of the discussion and pointing to some directions for future research activities.
Keywords: 330